Experimental Studies on Behavior of Keratin Based Human Hair Fiber - A New Reinforcing Material for Composites - Prasad K., Eshwara; Rao P., Divakara; Kiran C., Udaya (International Journal of Engineering and Technology, 2018)
Composite materials are formed by two or more constituents at macroscopic level. Type and form of fiber plays a vital role in imparting required properties to the composite. Many researchers contributed to the development of artificial fiber composites which are not environmental friendly in nature. Sizable research is also done in the area of natural fiber composites. Human hair is a non-biodegradable waste available in abundant quantity across the world, but is rarely explored for applications in engineering fields.Â In the present study, a review on behavior of human hair fibers was made to understand their suitability as a reinforcing material in composites. Morphology of the hair fibers is reviewed and the density of the hair fibers was determined using Archimedes principle. Tensile strength of the hair fibers is experimentally estimated. Chemical resistivity and burning tests were conducted. Tensile and flexural properties of hair fiber reinforced polyester composite were experimentally determined and compared.Â Â